If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 105 + -5x = 9x + 2 Reorder the terms: 105 + -5x = 2 + 9x Solving 105 + -5x = 2 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 105 + -5x + -9x = 2 + 9x + -9x Combine like terms: -5x + -9x = -14x 105 + -14x = 2 + 9x + -9x Combine like terms: 9x + -9x = 0 105 + -14x = 2 + 0 105 + -14x = 2 Add '-105' to each side of the equation. 105 + -105 + -14x = 2 + -105 Combine like terms: 105 + -105 = 0 0 + -14x = 2 + -105 -14x = 2 + -105 Combine like terms: 2 + -105 = -103 -14x = -103 Divide each side by '-14'. x = 7.357142857 Simplifying x = 7.357142857
| (3/16+5/9)*24/30 | | 3/4/y=-7/48 | | 100x+2000=200x | | 2(2.5+-4.5y)+9y=5 | | 5/2(1-2x)+15/2=-4x | | 3+2(2x+5)=0 | | 1.6h-72=-3d+2 | | 3x^3-147=0 | | 9s^2+11s+4=0 | | -3(8)-4(0)= | | 4(3y-3)=6y-24 | | -3(n-2)=3n-5+9 | | 2x-5(0)=16 | | 2ln(-x)+8=16 | | 2(8+2.5y)=16 | | -42=-36t | | 0-3(0)=6 | | 6t+2=2(3t+1) | | y=7-x/2 | | 3z^2+5z+1=3 | | 2x+x+4x=1715 | | 4x-3-6x+2=0 | | 0.25t+0.833=1.5t+0.67 | | (7-2j)-(7+2j)= | | 6x+8=4x+4-2x | | (y*2)+y=957 | | x+(x-3)=31 | | (x-3)(x-3)=20 | | 79-2x=10x-19 | | -5=z/3 | | 2g-32=-32 | | x-(x-1)=81 |